Strangers at home : Amish and Mennonite women in history - Schmidt, Kimberly D., 1961-; Umble, Diane Zimmerman; Reschly, Steven D. (Center books in Anabaptist studies., 2002)
""A major contribution to our understanding of Anabaptist history and the ongoing construction of Anabaptist identity."" -- Mennonite Quarterly Review.